MENINGKATKAN KEMAMPUAN MENULIS BAGIAN TUMBUHAN YANG DIDESKRIPSIKAN MELALUI PENDEKATAN CTL PADA ANAK TUNAGRAHITA RINGAN - Hasnita - Hasnita (Jurnal Penelitian Pendidikan Khusus, 2012)
This research of background overshadow by result of performed a antecedent study in SDLB Country 36 Muaro Sijunjung especially at child of tunagrahita light specially in class of II, where child in writing not yet used space, punctuation mark, sentence structure, there no according to between sentence in a paragraf and in writing sentence structure often  return, so that child get difficulty in writing the parts of plant which is description as according to its characteristics. As intention of this research, to know effective do not ithim execution of study pass/through approach of CTL ( Contextual Teaching Learning and) to increase ability write the parts of plant which is description in class of II SDLB Country 36 Muaro Sijunjung. This research use class action methodologies ( research action classroom) with berkolaborasi at friend of sejawat / other class teacher, and as research object is 3 ( class student people tiga) of II light tunagrahita at SDLB Country 36 Muaro Sijunjung Result of research of is existence of the make-up of in ability write the parts of plant which is description which enough signifikan if/when compared to the condition of early with data after treatment